Impact of Covid-19 and drought on the economy of therepublic of Moldova - Tamara Leah (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The paper characterizes the cumulative impact of the pandemic and drought on the main economic sectors of the Republic of Moldova. Total Gross Added Value (GAV) per economy, with a share of 87.0% in the Gross Domestic Product (GDP) formation, contributed to the decrease of GDP by 6.0% in 2020 compared to 2019, the volume of GAV being decreasing by 6.9%. Agriculture, which contributed more than 1/3 to the decrease of GDP (2.7%) with a share of 9.5% to the formation of GDP and a decrease of GAV on the respective activities by 26.4%. Following the drought impact, the second consecutive year, the share of agriculture in the structure of the economy is less than 10%. Trade, transport and storage, HoReCa contributed by -2.1% to the decrease of GDP, with a share of 20.7% to the formation of GDP and a decrease of GAV on the respective activities by 9.6%. These 3 sectors absorbed the shock of the pandemic the most, given that by far the most affected sectors are those involving the interaction and mobility of the population. Industry contributed by -0.6% to the decrease of GDP, with a share of 14.0% to the formation of GDP and a decrease of GAV on the respective activities by 4.3%. The negative result in the industry is also explained by the impact of the drought, which contributes to the increase in the price of raw materials for the food and beverage industry. Net taxes on products, with a share of 13.0% in GDP formation, contributed to the decrease of GDP by -1.0%, their volume decreasing by 7.3%. Despite the crisis of the last year, wages have risen more than prices. The cost of living in 2020 has remained virtually unchanged, if we refer to the insignificant inflation of 0.39%.
Keywords: Q01; F63; 330; GDP; GAV; drought; agriculture